Analisis Faktor-Faktor yang Mempengaruhi Kelancaran Pengembalian Pembiayaan Pada Anggota KSPPS BMT Al-Hikmah Jepara - Khazimatul Aliya; Silviana Pebruary (Jurnal Rekognisi Akuntansi, 2020)
KSPPS BMT Al Hikmah Jepara conducted a financing analysis for the capital to be disbursed so that the capital proved safe, smooth, and profitable. The study aimed to examine the effect of variable loan values, guarantees, age, education levels, partial and simultaneous family dependents on smooth return on financing. This research method is descriptively quantitative. The data analysis technique used is multiple linear regression data analysis. The population in this study was a member in KSPPS BMT Al-Hikmah Jepara period 2017-2019 as many as 51,193 members. The sample number was 100 respondents. The results showed that the value of loans, guarantees, age, and family dependents partially affected the smooth return of financing in KSPPS BMT member Al Hikmah Jepara. While the level of education has no effect on the smooth return of KSPPS BMT Al Hikmah Jepara financing. Loan value, guarantee, age, education level, family dependents simultaneously affect the smooth return of financing to KSPPS BMT member Al Hikmah Jepara